PERSEPSI INVESTOR TERHADAP PERUBAHAN PENYAJIAN KEPENTINGAN NONPENGENDALI SEBELUM DAN SESUDAH BERLAKU EFEKTIFNYA PSAK 4 (REVISI 2009) - Margaret, Margaret; Hidayat, Taufik (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
This study aims to examine investors’ perception toward changes in noncontrolling interest presentation before and after the effective date of PSAK 4 (Revised 2009). The perception is determined from the value relevance of noncontrolling interest component, whether the value relevance is negative (liabilities) or positive (equity). PSAK 4 (1994) regulated that noncontrolling interests should be presented as mezzanine items, meanwhile PSAK 4 (Revised 2009) regulated that noncontrolling interests should be presented as equity in consolidated statement of financial position. Sample of this study consists of 137 listed companies in Indonesia Stock Exchange (IDX) from various industry sectors with six years observation. This study used regression method for panel data. The result shows that before the effective date of PSAK 4 (Revised 2009), investors perceived noncontrolling interests as equal to liabilities. After the effective date of PSAK 4 (Revised 2009), changes in noncontrolling interests presentation as equity do not change investors’ perception as equity. This result gives evidence that changes in presentation of an item in financial statement do not necessarily change investors’ perception toward a financial statement item.